Academic freedom : the global challenge - Ignatieff, Michael; Roch, Stefan (Central European University Press, 2018)
"The conference "Academic Freedom - The Global Challenge" was held at Central European University, Budapest in June 2017. Academic freedom--the institutional autonomy of scientific, research and teaching institutions, and the freedom of individual scholars and researchers to pursue controversial research and publish controversial opinions--is a cornerstone of any free society. Today this freedom is under attack from the state in many countries--Russia, Turkey, Venezuela, Hungary, China--but it is also under question from within academe. Bitter disputes have erupted on American campuses, for example, about the limits of free speech and about whether liberal academic freedoms have degenerated into a form of coercive political correctness. Beyond the academy itself, among the general public, academic freedom is contested ground. As Robert Post of Yale Law School has put it, academic freedom is "the price the public must pay in return for the social good of advancing knowledge." Populist currents of political opinion are questioning the price a society pays for the freedom of its 'experts' and professors. This book on the topic of academic freedom seeks to clarify our understanding of what academic freedom is, why it is under attack, from without and from within, and what needs to be done to reform and revive an ideal which is central to democratic freedom itself"--